Standards - Gabriel Jacobs (Association for Learning Technology, 1993)
One of the aims of ALT is to promote good practice in the use of learning technology within higher education. Few would not subscribe to this aim, but proclaiming it without a full awareness of the problems it entails is of the same order as proclaiming one's commitment to Peace without further comment. Except for the absolute pacifist, being against war does not mean being against it at any price, but rather being committed to ensuring circumstances in which war will not occur. So it is with good practice in educational technology, which can be achieved only if circumstances are propitious. Such circumstances include sufficient funds, and a willingness in both teacher and learner to accept in whole or in part a technological route – good practice is unlikely to be achieved if technology has been incorporated into the curriculum merely in order to ensure that funds already spent do not appear to have been wasted. Above all, in my view, good practice assumes that users of learning technology are able to concentrate on learning without (necessarily) thinking about the technology, since if the technology cannot be made to work transparently, actual practice will at best lag behind ideal practice, and at worst be abandoned altogether. Impatience is a barrier to learning, and particularly if it is the result of struggling with the learning tools themselves. If the teacher or learner is constantly having to tweak the technology, or ending up with a half-baked implementation because the setting-up process has proven too difficult, the learning tool may well be left to gather dust.